IMPROVING THE WASTE MANAGEMENT SYSTEM IN SURKHANDARYA (Journal of Universal Science Research, 2023)
This article delves into the pressing issue of waste management in Surkhandarya, a region in southern Uzbekistan. It examines the existing waste management challenges, analyzes potential solutions, and outlines a comprehensive strategy to enhance the waste management system. The study draws upon literature analysis, expert opinions, and case studies to provide valuable insights for sustainable development in Surkhandarya.